2005
DOI: 10.1021/cm048363b
|View full text |Cite
|
Sign up to set email alerts
|

Deposition of GaSb Films from the Single-Source Precursor [t-Bu2GaSbEt2]2

Abstract: The potential application of [t-Bu2GaSbEt2]2 (1) to serve as a single-source precursor for the deposition of GaSb films was investigated in detail. Crystalline GaSb films (sphalerite type) were grown on Si(100) by high-vacuum metal−organic chemical vapor deposition between 350 and 550 °C without the use of any carrier gas. The thermal properties of 1 were investigated by differential scanning calorimetry and thermogravimetric analysis/differential thermal analysis, whereas the GaSb films were characterized in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…These results are significant improvements compared to those obtained with the reactor previously described [12]. Using this reactor, substrate temperatures between 450 and 550 1C were required and the surface of the resulting GaSb films was significantly rougher (about 200 nm).…”
Section: Article In Pressmentioning
confidence: 80%
See 1 more Smart Citation
“…These results are significant improvements compared to those obtained with the reactor previously described [12]. Using this reactor, substrate temperatures between 450 and 550 1C were required and the surface of the resulting GaSb films was significantly rougher (about 200 nm).…”
Section: Article In Pressmentioning
confidence: 80%
“…In addition, [t-Bu 2 GaSbEt 2 ] 2 sublimes without decomposition at 120 1C and 10 À5 mbar. Preliminary studies demonstrated its capability to serve as a single-source precursor for the deposition of GaSb films [12]. However, its low vapor pressure and air-and moisture sensitivity required the development of a new reactor system, which is described herein.…”
Section: Resultsmentioning
confidence: 99%
“…According to former differential scanning calorimetry (DSC) results [6] the precursor molecule shows thermal decomposition at 464 and 486 K. Thus, it should be possible to sublime the species without decomposition at lower temperatures. Monitoring the base pressure during evaporation shows an increasing pressure at temperatures above 370 K (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…During deposition the sample was heated to temperatures in the range of 670-770 K. In general lower deposition temperatures could be used, but then the quality of the produced films turned out to be rather low in terms of homogenous coverage [6]. After sputtering, the carbon contamination due to the precursors alkylgroups was removed (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation